Growth comparison of piglets fed with different level of bakery waste in basal diet - Tiwari, M. R.; Dhakal, H. R.; Sah Sudi, M. (Journal of Agriculture and Forestry University, 2020)
An experiment was done on weaned piglets at Piggery Research Unit of Regional Agricultural Research Station, Tarahara, Sunsari, NARC, during 6 January 2019 to 5 May 2019 for 120 days after adjustment period of seven days. Twenty piglets, after weaning at 4-6 months of age were allocated into four treatments, each with 5 replications by using Completely Randomized Design. Four types of diets were used as treatments. Bakery waste was not incorporated in the control group diet (T1) whereas in the diet of T2, T3 and T4 maize as an ingredient was replaced by 25, 50 and 75% with bakery waste, respectively. Concentrate mixture was provided in adlib amount twice a day and refusal was measured in next morning while body weight gain was measured at 15 days interval. The findings revealed that highest total body weight gain was observed when maize was replaced by bakery waste (50%) (T3).But the total body weight gain was statistically similar (p>0.05) among the treatments group. The average daily gain was also highest when maize as an ingredient was replaced by bakery waste 50% (T3) with the gain of 325 g/day. Total feed intake during experimental period was highest for the same treatment. Feed Conversion Ratio (FCR) of entire (120 days) experimental period was also statically similar (p>0.05) for all treatments (1kg body weight: 2kg feed). The findings thus suggested that replacement of maize as an ingredient by bakery waste in piglet diet could be beneficial if it is replaced by 50% compared to 25% or 75% inclusion. Further in depth research is required to assess the effectiveness of replacing maize and other important ingredients with bakery waste before recommending this practice to the piglet growers.